PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN MATEMATIKA MATERI BENTUK ALJABAR KELAS VII DENGAN PENDEKATAN PROBLEM BASED LEARNING - Ni'mah Nur'aini; Wahyu Setiawan; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the increase in student learning outcomes in each cycle by using a problem based learning approach. The study was conducted in class VII of SMP Negeri 16 Cimahi in the odd semester of the 2021/2022 academic year. The type of research used is Classroom Action Research (CAR), the research is carried out in cycle II. The initial stage of the researcher consists of the planning stage, the implementation stage, the observation stage and the reflection stage. The instrument used is a test in the form of questions and non-test by making observations. This research data processing uses the percentage formula with the help of microsoft excel. The research subjects were 14 seventh grade students from SMP Negeri 16 Cimahi in the 2021/2022 academic year. The results of this study stated that in cycles 1 and 2 there was an increase in student learning outcomes. In the first cycle of student learning outcomes that is equal to 35.7% and in cycle 2 there is an increase in student learning outcomes that is equal to 90.63%.